Metal matrix composite material and preparation method thereof
By mixing ethyl orthosilicate, silicate and aminosilane coupling agent with metal powder and heating treatment, a metal-based composite material with nanosilicon dioxide particles uniformly distributed inside the coupling agent insulating film is solved, and higher insulation and heat resistance are achieved.
Patent Information
- Application Number
- CN202411983459.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
AI Technical Summary
The traditional oxide coating is difficult to evenly distribute on the surface of the metal powder, resulting in poor insulation of the metal powder.
The coupling agent of orthosilicate, silicate and aminosilane are mixed with water to form an insulating agent solution, and then mixed with metal powder for heating treatment to form a metal-based composite material with nanosilicon dioxide particles uniformly distributed inside the coupling agent insulating film.
The heat resistance of the coupling agent insulating film is improved, thereby significantly improving the insulating property of the metal powder.
Smart Images

Figure CN119897460A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a metal-based composite material and a preparation method thereof. Background Art
[0002] Metal soft magnetic powder core is a common soft magnetic material, which is widely used in electronic communications, switching power supplies and other fields. Metal soft magnetic powder core adopts powder metallurgy to make metal powder, and is made through insulation coating, pressing molding, high-temperature heat treatment and other processes. It has the characteristics of low high-frequency eddy current loss, high magnetic permeability and high temperature stability. Among them, the insulation coating process is one of the key steps. Insulation coating refers to uniformly coating a layer of insulating film on the surface of magnetic particles to reduce the loss of magnetic powder core when used at high frequency. Generally, the insulation coating layer is required to be thin and uniform, with good bonding performance, high thermal stability and high resistivity to reduce the energy loss caused by eddy current loss. However, the traditional oxide coating layer is difficult to be evenly distributed on the surface of metal powder, resulting in poor insulation of metal powder. Summary of the invention
[0003] Based on this, it is necessary to provide a metal-based composite material and a preparation method thereof to address the problem of how to improve the insulation properties of metal powder.
[0004] A method for preparing a metal matrix composite material comprises the following steps:
[0005] Evenly mixing tetraethyl orthosilicate, silicate, aminosilane coupling agent and water, and obtaining an insulating agent solution after sufficient reaction;
[0006] The insulating agent solution and the metal powder are mixed evenly and then heated to obtain a passivation powder after sufficient reaction; and
[0007] The passivation powder is annealed to obtain a metal-based composite material, which includes metal powder, a coupling agent insulating film coated on the surface of the metal powder, and nano-silicon dioxide particles distributed inside the coupling agent insulating film.
[0008] In the preparation method of the above metal-based composite material, tetraethyl orthosilicate is hydrolyzed in an alkaline environment to form a network state precipitate, thereby forming nano-scale silica particles uniformly dispersed on the surface of the metal powder; silicate is used to provide an alkaline environment and participate in the gelation process of the tetraethyl orthosilicate hydrolysis solution, so that the spatial structure of the silica particle gel is a network. More importantly, it has the ability to prevent the growth of gel-state silica particles while participating in the gelation process, so that the final precipitated nano-silica particles are small in size and uniformly distributed inside the coupling agent insulating film on the surface of the metal powder; the presence of the aminosilane coupling agent, on the one hand, its aqueous solution is alkaline, and on the other hand, it can be dissolved in ethanol, one of the hydrolysis products of tetraethyl orthosilicate, so that ethanol does not exist alone in the physical space, avoiding the silicate in the aqueous solution from encountering pure ethanol to produce flocculent precipitates, so that the alkaline hydrolysis product of tetraethyl orthosilicate can exist stably. In the metal-based composite material prepared by the preparation method of the above metal-based composite material, the nano-silica particles are uniformly distributed inside the coupling agent insulating film, which improves the heat resistance of the coupling agent insulating film, thereby improving the insulation of the metal powder.
[0009] In a feasible implementation, the silicate includes a combination of one or more of sodium silicate and potassium silicate.
[0010] In a feasible implementation, the mass ratio of the sum of the silicate and the aminosilane coupling agent to the tetraethyl orthosilicate is 1:(1-3); and / or
[0011] The mass ratio of the silicate to the aminosilane coupling agent is 1:3 to 3:1.
[0012] In a feasible implementation, the mass ratio of the tetraethyl orthosilicate, the silicate, the aminosilane coupling agent and the metal powder is 1:100 to 1:40; and / or
[0013] The mass ratio of the ethyl orthosilicate, the silicate and the aminosilane coupling agent to the water is 1:4 to 1:2.
[0014] In a feasible implementation, the metal powder is selected from at least one of iron powder, iron-silicon series soft magnetic powder, iron-based amorphous soft magnetic powder, iron-based amorphous nanocrystalline powder, Fe50Ni50 series powder, copper powder, copper alloy powder, aluminum powder and aluminum alloy powder.
[0015] In a feasible implementation, after ethyl orthosilicate, silicate, aminosilane coupling agent and water are uniformly mixed, the temperature for full reaction is 25° C. to 45° C., and the pH value of the insulating agent solution is 11 to 14.
[0016] In a feasible implementation, the operation of heating after the insulating agent solution and metal powder are evenly mixed is as follows: pour the insulating agent solution into the metal powder and stir for 10 minutes to 60 minutes at a stirring temperature of 25°C to 45°C, and then maintain the heating temperature at 45°C to 120°C under stirring until the gel precipitates the silica particles and removes the water.
[0017] In a feasible implementation, the temperature of the annealing treatment is 220° C. to 400° C., the time of the annealing treatment is 60 minutes to 300 minutes, and the atmosphere of the annealing treatment is dry air, dry nitrogen or a vacuum environment.
[0018] In a feasible implementation, the size of the nano-silicon dioxide particles is ≤5 nm.
[0019] A metal matrix composite material is prepared by any of the above-mentioned methods for preparing the metal matrix composite material.
[0020] In the metal-based composite material prepared by the preparation method of the metal-based composite material, the nano-silicon dioxide particles are evenly distributed inside the coupling agent insulating film, which improves the heat resistance of the coupling agent insulating film and thus improves the insulation of the metal powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The present invention is a flowchart of a method for preparing a metal-based composite material according to an embodiment of the present invention. DETAILED DESCRIPTION
[0022] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0024] See also Figure 1 A method for preparing a metal matrix composite material according to an embodiment of the present invention comprises the following steps:
[0025] S10, uniformly mixing tetraethyl orthosilicate, silicate, aminosilane coupling agent and water, and obtaining an insulating agent solution after sufficient reaction.
[0026] Among them, ethyl orthosilicate is hydrolyzed in an alkaline environment to form a network state precipitate, thereby forming nano-scale silicon dioxide particles uniformly dispersed on the surface of the metal powder.
[0027] Among them, silicate is used to provide an alkaline environment, and silicate is the main contributor to the pH value. At the same time, it participates in the gelation process of the ethyl orthosilicate hydrolysis solution, so that the spatial structure of the silica particle gel is network-like. More importantly, it has the ability to prevent the growth of gel-state silica particles while participating in the gelation process, so that the final precipitated nano-silica particles are small in size and evenly distributed inside the coupling agent insulating film on the surface of the metal powder.
[0028] Among them, the presence of aminosilane coupling agent makes its aqueous solution alkaline on the one hand, and on the other hand it can be dissolved in ethanol, one of the hydrolysis products of tetraethyl orthosilicate, so that ethanol does not exist alone in the physical space, avoiding the silicate in the aqueous solution from generating flocculent precipitates when encountering pure ethanol, so that the alkaline hydrolysis product of tetraethyl orthosilicate can exist stably.
[0029] In a feasible implementation, the silicate includes a combination of one or more of sodium silicate and potassium silicate.
[0030] In a feasible implementation, the aminosilane coupling agent may be KH550, KH560, KH570, KH792 or DL602I.
[0031] In a feasible implementation, the mass ratio of the sum of silicate and aminosilane coupling agent to tetraethyl orthosilicate is 1:(1-3). Further, the mass ratio of the sum of silicate and aminosilane coupling agent to tetraethyl orthosilicate can be, but is not limited to, 1:1, 1:2 or 1:3.
[0032] In a feasible implementation, the mass ratio of silicate to aminosilane coupling agent is 1:3 to 3:1.
[0033] In a feasible implementation, the mass ratio of tetraethyl orthosilicate, silicate and aminosilane coupling agent to metal powder is 1:100 to 1:40. Further, the mass ratio of tetraethyl orthosilicate, silicate and aminosilane coupling agent to metal powder can be, but is not limited to, 1:100, 1:90, 1:80, 1:70, 1:60, 1:50 or 1:40.
[0034] In a feasible implementation, the mass ratio of ethyl orthosilicate, silicate and aminosilane coupling agent to water is 1:4 to 1:2. Further, the mass ratio of ethyl orthosilicate, silicate and aminosilane coupling agent to water can be, but is not limited to, 1:4, 1:3 or 1:2.
[0035] In a feasible implementation, the metal powder is selected from at least one of iron powder, iron-silicon series soft magnetic powder, iron-based amorphous soft magnetic powder, iron-based amorphous nanocrystalline powder, Fe50Ni50 series powder, copper powder, copper alloy powder, aluminum powder and aluminum alloy powder.
[0036] In a feasible implementation, after ethyl orthosilicate, silicate, aminosilane coupling agent and water are uniformly mixed, the temperature for full reaction is 25° C. to 45° C., and the pH value of the insulating agent solution is 11 to 14.
[0037] S20, mixing the insulating agent solution obtained in step S10 and the metal powder uniformly and then heating them to obtain passivation powder after sufficient reaction.
[0038] In a feasible implementation, the operation of heating after the insulating agent solution and the metal powder are evenly mixed is as follows: pour the insulating agent solution into the metal powder and stir for 10 to 60 minutes at a stirring temperature of 25°C to 45°C, and then maintain the heating temperature at 45°C to 120°C under stirring until the gel precipitates the silica particles and removes the water. This can remove unstable crystal water, thereby improving the thermal stability of silica.
[0039] S30, annealing the passivation powder obtained in step S20 to obtain a metal-based composite material, wherein the metal-based composite material includes metal powder, a coupling agent insulating film coated on the surface of the metal powder, and nano-silicon dioxide particles distributed inside the coupling agent insulating film.
[0040] Among them, the component of the coupling agent insulating film is aminosilane coupling agent. In the preparation method of the metal-based composite material of this embodiment, the order of the gelation process is: the large molecular weight ions of the hydrolyzed state of tetraethyl orthosilicate wrapped with the ionized silicate ions first gel into a jelly-like silicon dioxide network (most of the jelly is water), and the ionic coupling agent is also in the jelly-like substance. As the subsequent temperature rises, it gradually dehydrates and the jelly changes into a honeycomb; when the water is removed, the silicate exists in a granular state, and the aminosilane coupling agent exists in a liquid state and becomes a coupling agent insulating film coated on the surface of the metal powder; the nano-silicon dioxide obtained after the hydrolysis of tetraethyl orthosilicate is in a granular state and is evenly distributed inside the coupling agent insulating film.
[0041] In a feasible implementation, the annealing temperature is 220° C. to 400° C., the annealing time is 60 minutes to 300 minutes, and the annealing atmosphere is dry air, dry nitrogen or a vacuum environment.
[0042] In a feasible implementation, the size of the nano-silicon dioxide particles is ≤5 nm. Further, the size of the nano-silicon dioxide particles may be, but is not limited to, 1 nm, 2 nm, 3 nm, 4 nm or 5 nm.
[0043] In the preparation method of the above metal-based composite material, tetraethyl orthosilicate is hydrolyzed in an alkaline environment to form a network state precipitate, thereby forming nano-scale silica particles uniformly dispersed on the surface of the metal powder; silicate is used to provide an alkaline environment and participate in the gelation process of the tetraethyl orthosilicate hydrolysis solution, so that the spatial structure of the silica particle gel is a network. More importantly, it has the ability to prevent the growth of gel-state silica particles while participating in the gelation process, so that the final precipitated nano-silica particles are small in size and uniformly distributed inside the coupling agent insulating film on the surface of the metal powder; the presence of the aminosilane coupling agent, on the one hand, its aqueous solution is alkaline, and on the other hand, it can be dissolved in ethanol, one of the hydrolysis products of tetraethyl orthosilicate, so that ethanol does not exist alone in the physical space, avoiding the silicate in the aqueous solution from encountering pure ethanol to produce flocculent precipitates, so that the alkaline hydrolysis product of tetraethyl orthosilicate can exist stably. In the metal-based composite material prepared by the preparation method of the above metal-based composite material, the nano-silica particles are uniformly distributed inside the coupling agent insulating film, which improves the heat resistance of the coupling agent insulating film, thereby improving the insulation of the metal powder.
[0044] A metal-based composite material according to one embodiment is prepared by any of the above-mentioned methods for preparing a metal-based composite material.
[0045] In the metal-based composite material prepared by the preparation method of the metal-based composite material, the nano-silicon dioxide particles are evenly distributed inside the coupling agent insulating film, which improves the heat resistance of the coupling agent insulating film and thus improves the insulation of the metal powder.
[0046] With reference to the above implementation contents, in order to make the technical solution of the present invention more specific, clear and easy to understand, the technical solution of the present invention is now exemplified. However, it should be noted that the contents to be protected by the present invention are not limited to the following embodiments.
[0047] Example 1
[0048] In this embodiment, metal powder with a composition of Fe91.5Cr4.5Si5.0 prepared by water-gas combined atomization is used as raw material, and its average particle size (D50) is 10.0 μm and the tap density is 4.30 g / cm 3 .
[0049] Surface insulation treatment is referred to as passivation here, passivation agent selection:
[0050] ① The amount of ethyl orthosilicate added is 1.5% of the weight of the metal powder;
[0051] ② The amount of sodium silicate (Na2SiO4.9H2O) added is 0.5% of the weight of the metal powder, and the amount of KH550 coupling agent added is 0.2% of the weight of the metal powder;
[0052] ③ The diluent is pure water, and the added amount is 5% of the weight of the metal powder.
[0053] The preparation method of the metal matrix composite material of this embodiment is as follows:
[0054] (1) mixing tetraethyl orthosilicate, sodium silicate, KH550 coupling agent and water and stirring for 30 minutes to obtain an insulating agent solution;
[0055] (2) The passivation process is as follows:
[0056] ① Pour the metal powder into the insulating agent solution and stir for 15 minutes;
[0057] ② Start heating, set the temperature to 120℃, and continue stirring until the powder is dry;
[0058] The dried powder was baked at 120°C for 60 minutes to obtain a passivated powder;
[0059] (3) The passivated powder was annealed at 220° C., 300° C., 350° C., 400° C. and 450° C. in a vacuum environment for 1 hour to obtain the metal matrix composite material of Example 1.
[0060] DC resistance test:
[0061] (1) Weigh 2 g of the metal matrix composite material sample after insulation treatment, the outer diameter of the magnetic ring is 14 mm, the inner diameter is 8 mm, the sample is in a circular shape, and the molding pressure is 300 MPa;
[0062] (2) The magnetic ring is placed in a test fixture. The test instrument is a resistance tester with an output voltage of 10 V. The distance between the positive and negative poles is 10 mm. At this distance, the positive and negative contacts are brought into contact with the horizontal surface of the magnetic ring. The output is the resistance value, as shown in Table 1.
[0063] Table 1
[0064] Annealing temperature(℃) DC resistance(MΩ) <![CDATA[Magnetic ring density (g / cm 3 )]]> Unannealed 55 5.85 220 150 5.85 300 180 5.85 350 176 5.85 400 120 5.88 450 20 5.87
[0065] From the results in Table 1, it can be seen that the resistance of the unannealed state is lower than that of the annealed state, mainly due to the presence of crystal water, which has little effect on the density. When the annealing temperature is 450°C, the resistance is small, but it has little effect on the density, because there will be certain micro cracks in the structure after the crystal water is completely removed. Therefore, the results in Table 1 show that in the preparation method of the metal-based composite material of the present invention, when the annealing temperature is 220°C to 400°C, the resistance value is large, indicating that the insulation of the metal powder can be improved.
[0066] Example 2
[0067] In this embodiment, metal powder with a composition of Fe91.5Cr4.5Si5.0 prepared by water-gas combined atomization is used as raw material, and its average particle size (D50) is 10.0 μm and the tap density is 4.30 g / cm 3 .
[0068] Surface insulation treatment is referred to as passivation here, passivation agent selection:
[0069] ① The amount of ethyl orthosilicate added is 1.5% of the weight of the metal powder;
[0070] ② The addition amount of sodium silicate (Na2SiO4.9H2O) is 0.25%, 0.5%, and 0.75% of the weight of the metal powder, and the addition amount of KH550 coupling agent is 0.75%, 0.5%, and 0.25% respectively;
[0071] ③ The diluent is pure water, and the added amount is 5% of the weight of the metal powder.
[0072] The preparation method of the metal matrix composite material of this embodiment is as follows:
[0073] (1) mixing tetraethyl orthosilicate, sodium silicate, KH550 coupling agent and water and stirring for 30 minutes to obtain an insulating agent solution;
[0074] (2) The passivation process is as follows:
[0075] ① Pour the metal powder into the insulating agent solution and stir for 15 minutes;
[0076] ② Start heating, set the temperature to 120℃, and continue stirring until the powder is dry;
[0077] ③ Bake the dried powder at 120°C for 60 minutes to obtain passivated powder;
[0078] (3) The passivated powder was annealed at 350° C. for 1 hour in a vacuum environment to obtain the metal matrix composite material of Example 2.
[0079] DC resistance test:
[0080] (1) Weigh 2 g of the metal matrix composite material sample after insulation treatment, the outer diameter of the magnetic ring is 14 mm, the inner diameter is 8 mm, the sample is in a circular shape, and the molding pressure is 300 MPa;
[0081] (2) The magnetic ring is placed in a test fixture. The test instrument is a resistance tester with an output voltage of 10 V. The distance between the positive and negative poles is 10 mm. At this distance, the positive and negative contacts are in contact with the horizontal surface of the magnetic ring. The output is the resistance value, as shown in Table 2.
[0082] Table 2
[0083]
[0084] From the results in Table 2, it can be seen that the more sodium silicate, the lower the resistance. The main reason is the presence of sodium ions in sodium silicate. In addition, the more sodium silicate, the lower the density. When the mass ratio of sodium silicate to KH550 is 1:3, the resistance is the highest and the insulation is the best.
[0085] Example 3
[0086] In this embodiment, metal powder with a composition of Fe91.5Cr4.5Si5.0 prepared by water-gas combined atomization is used as raw material, and its average particle size (D50) is 10.0 μm and the tap density is 4.30 g / cm 3 .
[0087] Surface insulation treatment is referred to as passivation here, passivation agent selection:
[0088] ① The amount of ethyl orthosilicate added is 1.5% of the weight of the metal powder;
[0089] ② The addition amount of sodium silicate (Na2SiO4.9H2O) and KH550 coupling agent is 0.25%+0.25%, 0.375%+0.375%, 0.75%+0.75% of the weight of the metal powder respectively;
[0090] ③ The diluent is pure water, and the added amount is 5% of the weight of the metal powder;
[0091] The preparation method of the metal matrix composite material of this embodiment is as follows:
[0092] (1) mixing tetraethyl orthosilicate, sodium silicate, KH550 coupling agent and water and stirring for 30 minutes to obtain an insulating agent solution;
[0093] (2) The passivation process is as follows:
[0094] ① Pour the metal powder into the insulating agent solution and stir for 15 minutes;
[0095] ② Start heating, set the temperature to 120℃, and continue stirring until the powder is dry;
[0096] ③ Bake the dried powder at 120°C for 60 minutes to obtain passivated powder;
[0097] (3) The passivated powder was annealed at 220° C. for 1 hour in a vacuum environment to obtain the metal matrix composite material of Example 3.
[0098] DC resistance test:
[0099] (1) Weigh 2 g of the metal matrix composite material sample after insulation treatment, the outer diameter of the magnetic ring is 14 mm, the inner diameter is 8 mm, the sample is in a circular shape, and the molding pressure is 300 MPa;
[0100] (2) The magnetic ring is placed in a test fixture. The test instrument is a resistance tester with an output voltage of 10 V. The distance between the positive and negative poles is 10 mm. At this distance, the positive and negative contacts are in contact with the horizontal surface of the magnetic ring. The output is the resistance value, as shown in Table 3.
[0101] Table 3
[0102]
[0103] From the results in Table 3, it can be seen that the more ethyl orthosilicate is present, the higher the density is, and vice versa, the insulation increases. The main reason is that the presence of the coupling agent makes the insulation layer dense.
[0104] Example 4
[0105] In this embodiment, metal powder with a composition of Fe91.5Cr4.5Si5.0 prepared by water-gas combined atomization is used as raw material, and its average particle size (D50) is 10.0 μm and the tap density is 4.30 g / cm 3 .
[0106] Surface insulation treatment is referred to as passivation here. Passivators are divided into five groups:
[0107] ① The addition amount of ethyl orthosilicate in groups 1-5 is 0.3%, 0.6%, 0.9%, 1.5% and 1.8% of the weight of the metal powder respectively;
[0108] ② Groups 1-5 of sodium silicate (Na2SiO4.9H2O) are 0.1%, 0.2%, 0.3%, 0.5% and 0.6% of the weight of the metal powder respectively;
[0109] ③ Groups 1-5 KH550 (Na2SiO4.9H2O) are 0.1%, 0.2%, 0.3%, 0.5%, and 0.6% of the weight of the metal powder respectively;
[0110] ④ The diluent is pure water, and the added amount is 5% of the weight of the metal powder;
[0111] The preparation method of the metal matrix composite material of this embodiment is as follows:
[0112] (1) Mixing tetraethyl orthosilicate, sodium silicate, KH550 and water and stirring for 30 minutes to obtain an insulating agent solution;
[0113] (2) The passivation process is as follows:
[0114] ① Pour the metal powder into the insulating agent solution and stir for 15 minutes;
[0115] ② Start heating, set the temperature to 120℃, and continue stirring until the powder is dry;
[0116] ③ Bake the dried powder at 120°C for 60 minutes to obtain passivated powder;
[0117] (3) The passivated powder was annealed at 350° C. for 1 hour in a vacuum environment to obtain the metal matrix composite material of Example 4.
[0118] DC resistance test:
[0119] (1) Weigh 2 g of the metal matrix composite material sample after insulation treatment, the outer diameter of the magnetic ring is 14 mm, the inner diameter is 8 mm, the sample is in a circular shape, and the molding pressure is 300 MPa;
[0120] (2) The magnetic ring is placed in a test fixture. The test instrument is a resistance tester with an output voltage of 10 V. The distance between the positive and negative poles is 10 mm. At this distance, the positive and negative contacts are in contact with the horizontal surface of the magnetic ring. The output is the resistance value, as shown in Table 4.
[0121] Table 4
[0122]
[0123] Among them, the total amount of insulating agent is the sum of the masses of tetraethyl orthosilicate, sodium silicate and KH550 coupling agent.
[0124] From the results in Table 4, it can be seen that the more the total amount of insulating agent, the higher the resistance, but the density decreases.
[0125] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0126] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a metal matrix composite material, characterized in that: The steps include: Evenly mixing tetraethyl orthosilicate, silicate, aminosilane coupling agent and water, and obtaining an insulating agent solution after sufficient reaction; The insulating agent solution and the metal powder are mixed evenly and then heated to obtain a passivation powder after sufficient reaction; and The passivation powder is annealed to obtain a metal-based composite material, which includes metal powder, a coupling agent insulating film coated on the surface of the metal powder, and nano-silicon dioxide particles distributed inside the coupling agent insulating film.
2. The method for preparing the metal matrix composite material according to claim 1, characterized in that: The silicate includes a combination of one or more of sodium silicate and potassium silicate.
3. The method for preparing the metal matrix composite material according to claim 1, characterized in that: The mass ratio of the silicate to the aminosilane coupling agent and to the tetraethyl orthosilicate is 1:(1-3); and / or The mass ratio of the silicate to the aminosilane coupling agent is 1:3 to 3:
1.
4. The method for preparing the metal matrix composite material according to claim 1, characterized in that: The mass ratio of the tetraethyl orthosilicate, the silicate, the aminosilane coupling agent and the metal powder is 1:100 to 1:40; and / or The mass ratio of the ethyl orthosilicate, the silicate and the aminosilane coupling agent to the water is 1:4 to 1:
2.
5. The method for preparing the metal matrix composite material according to claim 1 or 4, characterized in that: The metal powder is selected from at least one of iron powder, iron-silicon series soft magnetic powder, iron-based amorphous soft magnetic powder, iron-based amorphous nanocrystalline powder, Fe50Ni50 series powder, copper powder, copper alloy powder, aluminum powder and aluminum alloy powder.
6. The method for preparing the metal matrix composite material according to claim 1, characterized in that: The temperature for fully reacting the tetraethyl orthosilicate, silicate, aminosilane coupling agent and water after being uniformly mixed is 25° C. to 45° C., and the pH value of the insulating agent solution is 11 to 14.
7. The method for preparing the metal matrix composite material according to claim 1, characterized in that: The operation of heating the insulating agent solution and the metal powder after being evenly mixed is as follows: pour the insulating agent solution into the metal powder and stir for 10 minutes to 60 minutes at a stirring temperature of 25°C to 45°C, and then maintain the heating temperature at 45°C to 120°C under stirring until the gel precipitates the silica particles and removes the water.
8. The method for preparing the metal matrix composite material according to claim 1, characterized in that: The temperature of the annealing treatment is 220° C. to 400° C., the time of the annealing treatment is 60 minutes to 300 minutes, and the atmosphere of the annealing treatment is dry air, dry nitrogen or a vacuum environment.
9. The method for preparing the metal matrix composite material according to claim 1, characterized in that: The size of the nano silicon dioxide particles is ≤5nm.
10. A metal matrix composite material, characterized in that: The metal matrix composite material is prepared by the preparation method of any one of claims 1 to 9.